2010
DOI: 10.1152/ajpcell.00253.2009
|View full text |Cite
|
Sign up to set email alerts
|

Retinal metabolic state of the proline-23-histidine rat model of retinitis pigmentosa

Abstract: -We determined the metabolic changes that precede cell death in the dystrophic proline-23-histidine (P23H) line 3 (P23H-3) rat retina compared with the normal SpragueDawley (SD) rat retina. Metabolite levels and metabolic enzymes were analyzed early in development and during the early stages of degeneration in the P23H-3 retina. Control and degenerating retinas showed an age-dependent change in metabolite levels and enzymatic activity, particularly around the time when phototransduction was activated. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…Notably, the remaining photoreceptors were left in a chronically hyperoxic environment which the authors proposed could lead to accelerated photoreceptor death via oxidative stress. In the developing P23H-3 retina, photoreceptor apoptosis was accompanied by increased metabolic activity, including elevated levels of lactate dehydrogenase, ATPase activity, and ATP, representing a potential cause of photoreceptor death (Acosta et al, 2010 ). An increase in dark-adapted photoreceptor cAMP levels was also observed in the P23H rats, which was potentially toxic and capable Mapping cation entry in photoreceptors and inner retinal neurons during early degeneration in the P23H-3 rat retina of promoting cell death (Traverso et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the remaining photoreceptors were left in a chronically hyperoxic environment which the authors proposed could lead to accelerated photoreceptor death via oxidative stress. In the developing P23H-3 retina, photoreceptor apoptosis was accompanied by increased metabolic activity, including elevated levels of lactate dehydrogenase, ATPase activity, and ATP, representing a potential cause of photoreceptor death (Acosta et al, 2010 ). An increase in dark-adapted photoreceptor cAMP levels was also observed in the P23H rats, which was potentially toxic and capable Mapping cation entry in photoreceptors and inner retinal neurons during early degeneration in the P23H-3 rat retina of promoting cell death (Traverso et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lactate concentration in the blood was determined using a lactate assay kit, as described previously (Acosta et al, 2010). Whole blood were homogenized in 0.9% saline and centrifuged at 2,800 g for 6 min, and the supernatant was diluted to 1:7 with saline.…”
Section: Methods Of Samples Analysismentioning
confidence: 99%
“…The averaged percentage change across ages is small but significant (P1 ϭ 8%, P4 ϭ Ϫ3%, P6 ϭ 2%, P10 ϭ 18%, P12 ϭ 3%, P15 ϭ 4%, P17 ϭ 13%, P21 ϭ 22%). Statistical analysis using two-way ANOVA showed that LDH activity between P1 and P21 was significantly higher in the P23H-3 than in SD retinas (P Ͻ 0.01) (2).…”
Section: Are Ldh Levels Significantly Elevated In the P23h Rat Retina?mentioning
confidence: 94%